Ability of inactivated vaccines based on far‐eastern tick‐borne encephalitis virus strains to induce humoral immune response in originally seropositive and seronegative recipients. Issue 2 (28th October 2018) - Maikova, Galina B.; Chernokhaeva, Liubov L.; Rogova, Yulia V.; Kozlovskaya, Liubov I.; Kholodilov, Ivan S.; Romanenko, Victor V.; Esyunina, Mariya S.; Ankudinova, Anna A.; Kilyachina, Anna S.; Vorovitch, Mikhail F.; Karganova, Galina G.
Abstract : Tick‐borne encephalitis (TBE) remains one of the major public health concerns in northern Eurasia, and its' area is expanding. TBE virus (TBEV) includes three subtypes and several monophyletic groups, cocirculating in Russia. Five inactivated vaccines are used for TBE prophylaxis. The rising number of people subjected to vaccination brings up the issue of the impact of individual recipient characteristics on vaccination efficacy. The present work studies correlations among the vaccination scheme, sex, age, body mass index (BMI), chronic diseases, postvaccinal reaction, pre‐existing anti‐TBEV antibodies, and postvaccinal humoral immunity development. Sera were collected during clinical trials in the TBEV Siberian subtype endemic area. Adult recipients were vaccinated with Tick‐E‐Vac and EnceVir vaccines based on Far‐Eastern TBEV strains. Vaccine ability to induce humoral immunity in different categories of recipients was estimated by seroconversion rates and the percentage of recipients with high neutralizing antibody titers (≥1:500). High immunogenicity of vaccines based on Far‐Eastern TBEV strains in the TBEV Siberian subtype endemic area in all groups of recipients was demonstrated. Impact of pre‐existing contact with the virus and high BMI on humoral immune response development 14 days after the first immunization was evidenced. Nevertheless, the difference was significantly less pronounced 30 days after the first vaccination and undetectable after the second one. Abstract : 1. Recipients with pre?existing contact with the virus showed higher percent of people with htnAb after the 1st vaccination. 2. Recipients with high BMI showed lower percent of people with htnAb after the 1st vaccination. 3. All studied individual characteristics did not have impact on the humoral immunity when evaluated after the 2nd vaccination.